Case report Hemosiderin pigmentation of tumour cells in cerebellar pilocytic astrocytoma associated with post-traumatic hemorrhage in adults - Taraszewska, Anna; Czernicki, Zbigniew; Andrychowski, Jarosław (Folia Neuropathologica, 2005)
The pilocytic astrocytoma is only rarely associated with gross intratumoral hemorrhage despite rich vasculature and blood vessel changes, accompanied often by perivascular depots of hemosiderin. We report an unusual case of pigmented cerebellar pilocytic astrocytoma presenting with posttraumatic hemorrhage in a 38-year-old man with no history related to the tumor. CT and MRI examination after head injury demonstrated unexpectedly the cystic lesion of 2 cm in diameter in the region of the right cerebellar hemisphere and vermis. The lesion was associated with hematoma and it was surgically removed 3 weeks after trauma. Histopathological examination revealed pilocytic astrocytoma tissue with broad hemorrhagic changes and with an unusual pattern of massive pigmentation of the cytoplasm of pilocytic astrocytes, consistent with hemosiderosis. Positive stains for iron and ferritin and ultrastructural study confirmed deposition of hemosiderin granules in the tumour cells. There was no evidence of melanin or melanosomes. This finding of hemosiderin accumulation in the cytoplasm of neoplastic astroglia seems to be analogous to post-hemorrhagic pigmentation of the normal Bergmann glia and subpial astrocytes. In the literature, the examples of neuroepithelial tumors with hemosiderin pigmentation of tumor cells have been rarely documented. To our knowledge, this is the first reported case of pigmented pilocytic astrocytoma exhibiting extensive intracellular hemosiderin deposition.